2017
DOI: 10.20302/nc.2017.26.21
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the flora of railway stations in the Mediterranean and sub-Mediterranean areas of Croatia and Bosnia and Herzegovina.

Abstract: The main aims of our study were (1) to determine the flora in railway areas with special emphasis on the presence of neophytes; (2) to describe the features of the flora through analyses of taxonomic composition, chorotypes, life forms and the phytosociological character of species found at 15 stations in the Mediterranean and sub-Mediterranean areas of Croatia and Bosnia and Herzegovina (SE Europe). According to their floristic composition, two broad groups of stations were recognized: i) stations in the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In the present study, neophytes contributed 10 % of identified flora. This is only partly consistent with the proportion of neophytes in urban flora of the main Croatian coastal cities (Jasprica et al, 2010(Jasprica et al, , 2017Milović & Mitić, 2012). In general, the pattern of neophytes is most strongly influenced by site conditions (Šilc et al, 2012).…”
Section: Discussionmentioning
confidence: 68%
“…In the present study, neophytes contributed 10 % of identified flora. This is only partly consistent with the proportion of neophytes in urban flora of the main Croatian coastal cities (Jasprica et al, 2010(Jasprica et al, , 2017Milović & Mitić, 2012). In general, the pattern of neophytes is most strongly influenced by site conditions (Šilc et al, 2012).…”
Section: Discussionmentioning
confidence: 68%
“…According to Denisow et al (2017), Jehlík et al (2017), Vinogradova et al (2017, Májeková et al (2021) synanthropic plants connected with human activity find suitable conditions also on railway. On the other hand, some native thermophilous species, rare and threatened plants (Novinska and Czarna 2008;Májeková et al 2014;Jasprica et al 2017;Vinogradova et al 2017) typical for other habitats are also occurred here. The authors present four species (Euphorbia davidii, Galeopsis angustifolia, Geranium purpureum, Grindelia squarrosa) that are typical examples of ferroviatic migration either in Slovakia or Ukraine.…”
Section: The Main Contribution Of the Presented Studiesmentioning
confidence: 70%
“…Most likely, it was introduced by rail transport or with track ballast during the renovation of railway tracks near the Bonarka station. The spread of G. rotundifolium into railway areas has already been observed in Poland (Trojecka-Brzezińska 2017), as well as in other European countries (Májeková et al 2014;Jasprica et al 2017;Leach 2020). Further long-term observations are required to confirm the establishment of the species in the Polish flora.…”
Section: Monika Majerová (Report 171)mentioning
confidence: 88%